An investigation into the behaviour, kinetics & mechanisms involved in the precipitation of a moderately soluble system - Musil, Emily Ann (Department of Chemical Engineering, 2014)
This dissertation consists of three interrelated sections dealing with: (i) Development of a suitable seed preparation technique, (ii) Determination of growth and aggregation kinetics and (iii) Determination of the induction period.